2006
DOI: 10.1590/s0104-11692006000300010
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients with spinal cord injuries and occurrence of pressure ulcer at a university hospital

Abstract: Patients with traumatic spinal cord injury (TSCI) have an increased risk of developing pressure ulcers (PU). It is a retrospective study done by review of records in order to identify the characteristics of patients who were assisted at a tertiary hospital as well as the occurrence of PU. Most patients were male, white and 36,2% between 21 and 30 years. The most common causes of TSCI were wound by fire weapons followed by vehicle crash/overturn. There was a predominance of injury at the toracic level followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
1
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 7 publications
(13 reference statements)
3
13
1
13
Order By: Relevance
“…With regard to the sociodemographic characteris cs of individuals with TSCI, these were highlighted by other studies repor ng that the popula on most aff ected by TSCI is that of young adults, aged 18 to 35 years, and overwhelmingly of the male gender (1,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 98%
“…With regard to the sociodemographic characteris cs of individuals with TSCI, these were highlighted by other studies repor ng that the popula on most aff ected by TSCI is that of young adults, aged 18 to 35 years, and overwhelmingly of the male gender (1,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 98%
“…3,6,10,11 Em relação às causas da LME, acidentes com veículo automotores e atos de violência têm sido observados no Brasil como frequente fator causal. 3,6,10,11 Os resultados da MIF mostraram que os indivíduos com LME em nível cervical, apresentaram valores menores dos escores quando Segundo as diretrizes para a prática clínica do CSCM 8 em relação ao autocuidado intestinal, paciente com LME C1 a C5 são totalmente dependentes de um cuidador, C6 a C8 necessitam de assistência parcial de um cuidador, de T1 a T9 espera-se pela independência funcional, T10 a L1 e L2 a S5 também são independentes no cuidado intestinal em condições adequadas. 8 Assim, o exame neurológico deve ser realizado e compartilhado entre os multiprofissionais a fim de se estabelecer metas a serem alcançadas no processo de reabilitação.…”
Section: Discussionunclassified
“…Observa-se, portanto, uma grande incapacidade que afeta uma população jovem e ativa, de forma repentina ocasionando repercussões psicobiológi-cas e psicossociais. 2,3 Assim, o processo de reabilitação deve ser iniciado desde a fase aguda, nas unidades de terapia intensiva, para evitar complicações que podem ser catastróficas e onerosas. 2 É necessário conhecer as características dos indivíduos com LME em termos de independência funcional, pois isso possibilita aos profissionais e aos centros de reabilitação estruturar-se para atenderem às demandas da população de forma mais efetiva e eficiente.…”
Section: Introductionunclassified
“…In the international literature, a study conducted in the Netherlands found that the incidence of PU was 10.9%, (6) and in Australia it was 18% (7) . In Brazil, for chronically ill and bedridden patients hospitalized in general hospitals, research has indicated incidence values between 17.7% and 39.8% (8,9) , and in a study conducted with patients with spinal cord injuries admitted to a teaching hospital, the authors identified the occurrence of PU in 42.5% (10) of the subjects investigated.…”
Section: Introductionmentioning
confidence: 99%